The mathematics for Engineers problem solver : (Research and Education Association, 1992)
The book is subdivided in to 12 chapters, each dealing with a separate topic. The subject matter is developed beginning with differential equations and extending through linear differential equations, applications of diffrential equations, vectors, multiple integrals, sequence and series, laplace transforms, and fourier transforms.